Early Neonatal Mortality (< 24 h) in Ecuador: A Population-Based Study on the Impact of Apgar Score, Gestational Age, Birth Weight, Delivery Type, and Healthcare Level - Iván Dueñas-Espín; María Alejandra Montaluisa; Andrea Aguilar-Molina; Fernando Aguinaga; Luciana Armijos-Acurio; Ruth Jimbo-Sotomayor; Ángela León Cáceres; María F. Rivadeneira; Silvana Rivera-Guerra; Xavier Sánchez; Betzabé Tello (International Journal of Pediatrics)
Conclusions: This study demonstrated that the Apgar score, among other determinants, was significantly associated with early neonatal mortality (before the first 24 h). This association was independent of type of delivery, comorbidities, disorders related to asphyxia, prematurity, infections, and other medical disorders, as well as varying levels of care from primary to tertiary. These findings underscore the importance of Apgar evaluation in neonates and suggest a predictive value of the score for early neonatal mortality.